"An Unspoken Level of Comfort": Black Therapists' Experiences Working With Black Clients. (February 2016) - Goode-Cross, David T.; Grim, Karen Ann
This study examined 36 Black therapists' experiences working with Black clients in hospital, school, college, and community counseling settings. Findings of this interpretative phenomenological analysis suggest these therapists most often feel a distinct sense of solidarity with their Black clients, as evidenced by having a better understanding of the context of Black clients' lives, creating easier and faster therapeutic connections with Black clients, and feeling especially committed to these clients' well-being. Participants also acknowledged the potential pitfalls and having insufficient boundaries and acknowledged the limitations of their formal training in learning to work with Black clients. How participant responses differed according to years of experience, practice setting, and gender are also explored. This study also suggests implications to increase the quality of training provided to therapist trainees of African descent.